2018
DOI: 10.1002/wps.20490
|View full text |Cite
|
Sign up to set email alerts
|

What causes psychosis? An umbrella review of risk and protective factors

Abstract: Psychosis is a heterogeneous psychiatric condition for which a multitude of risk and protective factors have been suggested. This umbrella review aimed to classify the strength of evidence for the associations between each factor and psychotic disorders whilst controlling for several biases. The Web of Knowledge database was searched to identify systematic reviews and meta-analyses of observational studies which examined associations between socio-demographic, parental, perinatal, later factors or antecedents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
506
3
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 446 publications
(543 citation statements)
references
References 149 publications
23
506
3
11
Order By: Relevance
“…For example, in our review we found that childhood trauma was considered as a common risk factor for psychosis,13 but available literature lacked standard operationalisation. Our pragmatic approach was to define the factors as each meta-analysis or systematic review had defined them.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, in our review we found that childhood trauma was considered as a common risk factor for psychosis,13 but available literature lacked standard operationalisation. Our pragmatic approach was to define the factors as each meta-analysis or systematic review had defined them.…”
Section: Resultsmentioning
confidence: 99%
“…Second, a clear link between the need to address uncertainty and advancing clinical knowledge should be identified a priori, and acknowledged as the strong rationale for conducting an umbrella review. For example, in our previous work we speculated that by clarifying the evidence for an association between risk or protective factors and psychotic disorders we could improve our ability to identify those individuals at risk of developing psychosis 13. Clearly, improving the detection of individuals at risk is the first step towards the implementation of preventive approaches, which are becoming a cornerstone of medicine 14–16.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations